2010
DOI: 10.4322/floram.2011.002
|View full text |Cite
|
Sign up to set email alerts
|

Technological Characterization of Cupressus spp. Wood 

Abstract: The objectives of the present study were to determine anatomical characteristics, mechanical properties and natural durability to two fungi types [Gloeophyllum trabeum (Persoon ex Fries) Murrill and Trametes versicolor (Linnaeus ex Fries)Pilat] for cypress wood (Cupressus spp.). The wood has straight grain, brown to white color, medium texture, and moderate luster. It also showed medium to low density, low shrinkage, and moderate dimensional stability. Lignin content was relatively high, whereas extractive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
3
5
0
3
Order By: Relevance
“…However, the holocellulose content obtained was lower than what is expected for the species, and also low when compared to other conifer species. Okino et al (2010) reported that, for the same species and with similar age 71,8% holocellulose values were observed, corroborating with Foelkel and Zvinakevicius (1975), who obtained 71,6% holocellulose and , using 56 years old C. lusitanica wood obtained 62,6% holocellulose.…”
Section: Chemical Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…However, the holocellulose content obtained was lower than what is expected for the species, and also low when compared to other conifer species. Okino et al (2010) reported that, for the same species and with similar age 71,8% holocellulose values were observed, corroborating with Foelkel and Zvinakevicius (1975), who obtained 71,6% holocellulose and , using 56 years old C. lusitanica wood obtained 62,6% holocellulose.…”
Section: Chemical Analysissupporting
confidence: 77%
“…Likewise, found 7,3% total extractives in 56 years old C. lusitanica plantations, while Okino et al (2010) found a mean value of 4,1% for total extractives, a very close value to the one obtained in this study. In a study with C. lusitanica, C. arizonica and C. sempervirens, Santos et al (2014) observed total extractives values of 3,87; 2,46 and 3,34% respectively.…”
Section: Chemical Analysissupporting
confidence: 64%
“…In Roman times, cypress wood was largely used in shipbuilding and other structures in long contact with water (Allevato et al, 2009;Colaianni et al, 2011;Sadori et al, 2015). Cupressus wood is known for its resistance to fungal activity in humid environments (Okino et al, 2010) and its use in shipbuilding, well lining etc., indicates that this property was already recognised in ancient times. Several wrecks revealed the use of cypress wood in ancient naval architecture such as a plank and a wale in Fiumicino 1 (Boetto, 2008), the keel in the Bourse wreck in Marseilles (Rival, 1991), planks and wales in Pantano Longarini (Kampbell, 2007).…”
Section: Cypress Wood Use In Ancient Architecturementioning
confidence: 99%
“…Its light color, anatomical characteristics and easy processing, makes it comparable to some common and commercial hardwood and softwood species, mainly Pinus spp., (Okino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%